Do Demographic Make a Difference to Job Burnout Among University Academicians? - Khan, Faisal; Rasli, Amran MD; Yusoff, Rosman Md; Ahmad, Aqeel (International Journal of Economics and Financial Issues, 2015)
The study examined the relationship between demographic variables and burnout dimensions and their effect among the academicians at universities in Pakistan. A questionnaire-based study was carried out from 265. By using statistical techniques like descriptive analysis, the result shows that the young academicians have high levels of burnout level, and revealed that there is no difference found regarding gender and marital status on the level of burnout. This study reported that age, experience and designation have a significant relationship with burnout dimensions. The study also examined implications, limitation and recommendation for future research. Keywords: Emotional Exhaustion, Disengagement, Academicians, Demographic Variables JEL Classifications: M00